BUKU SAKU VERSI ANDROID DAN iOS P3B PADANG BINTUNGAN KECAMATAN SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - Yanuarafi, Arisal (UIN Imam Bonjol Padang, 2022)
The Jorong Padang Bintungan youth has always been known as a creative, cooperative, unified and energetic youth. Until now, there are still many activities that are carried out together to achieve the goals that have been mutually agreed upon. In order to continue to transmit this spirit to the next generation, a thought is needed to be able to document heroic stories or complete stories about characters, places, and events so that they can be told later by their children and grandchildren. This research was developed using mobile programming to be running on Android and iOS devices. From this study, it was found that there was an increase in the interest of young people to know the history around Jorong Padang Bintungan.